The Efficacy and Safety of Selective Serotonin Reuptake Inhibitors and Serotonin-Norepinephrine Reuptake Inhibitors in the Treatment of Menopausal Hot Flashes: A Systematic Review of Clinical Trials - Marzieh Azizi; Soghra Khani; Mahsa Kamali; Forouzan Elyasi (Iranian Journal of Medical Sciences, 2022)
Background: Hot flashes (HF) are a common symptom during the menopausal transition. It is therefore important to identify effective drugs that can alleviate HF. This study aimed to systematically review published clinical trials on the efficacy and safety of selective serotonin reuptake inhibitors (SSRIs) and serotonin-norepinephrine reuptake inhibitors (SNRIs) in the treatment of HF in healthy menopausal women.Methods: In this systematic review, articles published during 2003-2019 in PubMed, MEDLINE, Web of Science, Scopus, Science Direct, PsycINFO, CINAHL, the Cochrane Central Register of Controlled Trials, and Google Scholar as well as Iranian databases such as SID, and Magiran were searched. The quality of the selected articles was assessed using the Jadad score calculation. Results: Thirty-six articles on randomized controlled trials were included in this study, out of which 27 articles had acceptable, and nine had weak methodological quality. Findings on SSRIs class of drugs indicated that escitalopram, paroxetine, and fluoxetine have higher efficacy and safety in the treatment of menopausal HF than other drugs. Studies on the effectiveness of sertraline, citalopram, and fluvoxamine are limited in number or show inconsistent results. Therefore, further high-quality studies are required to confirm their effectiveness in alleviating HF. Within the SNRIs class, venlafaxine and desvenlafaxine showed significant efficacy in the treatment of menopausal HF. However, studies on the effectiveness of duloxetine are also limited, which requires further research. Conclusion: Most studies have indicated the efficacy and safety of some antidepressants, such as SSRIs and SNRIs, in decreasing the frequency and severity of HF. These drugs are therefore recommended for the treatment of menopausal HF.